Using pocket science to learn together on the Uncompahgre Plateau - Matonis, Megan, author (Colorado State University. Libraries, 2014)
Megan will discuss the use of pocket science to engage citizens in asking ecological questions and learning about historical forest structure on the Uncompahgre Plateau. Pocket science involves the collection of simple and smart observations to learn from management activities. It's not expensive and complicated like rocket science! All you need are simple tools like a GPS unit and camera, and more importantly, an inquisitive mind open to surprises and new insights.
Presented at the Spring 2014 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Collaborative Conservation in Practice: Innovations in Communities around the World", April 15, 2014, Colorado State University, Fort Collins, Colorado. This series focused on the work that the CCC's Collaborative Conservation Fellows have been doing across the Western U.S. and around the world.
Megan Matonis is a PhD student working with Dan Binkley in the Graduate Degree Program in Ecology at Colorado State University. She is also a Graduate Student Cooperator with the Rocky Mountain Research Station. Her dissertation research focuses on the development and use of locally-relevant ecological information to empower collaborative forest restoration. Megan worked for the Forest Service Policy Analysis staff in Washington, DC after receiving a master's in forestry from Michigan State University.
PowerPoint presentation.